Volker Grieb, Krzysztof Nawotka and Agnieszka Wojciechowska (eds). Alexander the Great and Egypt: history, art, tradition - Barringer, Judith M. (Journal of Greek Archaeology, 2016)
This volume, comprised of twenty-two papers delivered at a two-day conference in Wrocław/Breslau in 2011, belongs to the series ‘Contributions to the Study of Ancient World Cultures.’ The goal of the conference was to investigate Egypt under Alexander and his successors, particularly the concept of Alexander as pharaoh, from an Egyptian viewpoint and using largely Egyptian sources, rather than the more common Hellenistic or Macedonian approach. These aims have largely been achieved in this collection of papers on wide-ranging but often highly specialized topics.